Sex differences underlying preexisting cardiovascular disease and cardiovascular injury in COVID-19 (2020)
The novel 2019 coronavirus disease (COVID-19), resulting from severe acute respiratory syndrome coronarvirus2 (SARS-CoV-2) infection, typically leads to respiratory failure in severe cases; however, cardiovascular injury is reported to contribute to a substantial proportion of COVID-19 deaths. Preexisting cardiovascular disease (CVD) is among the most common risk factors for hospitalization and death in COVID-19 patients, and the pathogenic mechanisms of COVID-19 disease progression itself may promote the development of cardiovascular injury, increasing risk of in-hospital death. Sex differences in COVID-19 are becoming more apparent as mounting data indicate that males seem to be disproportionately at risk of severe COVID-19 outcome due to preexisting CVD and COVID-19-related cardiovascular injury. In this review, we will provide a basic science perspective on current clinical observations in this rapidly evolving field and discuss the interplay sex differences, preexisting CVD and COVID-19-related cardiac injury